Competency-based education for school conflict resolution among Primary education teachers’ trainees - Padilla Hidalgo, M. Sc. Yailen; López Mejías, Dr. C. Modesta (Transformación, 2021)
Objective: This article aims at presenting a pedagogical intervention program for a competencybased education of conflict resolution by teachers’ trainee at the University of Camagüey. Methods: The authoress rely on methods such as the historical-logical, the analysis-synthesis, induction-deduction, documentary analysis and the systemic-structural-functional. Result: The main finding is a program for intervention for conflict resolution. The devised program is based on a pedagogic model that relates subjects’ knowledge, attitudes and experiences. It contributes to the education and performance of teachers’ trainees satisfying social demands. Conclusion: The pedagogical model and the program devised show that competency-based education of conflict resolution requires a contextualized close relation between theoretical, practical-experiential and attitudinal change components. As well as a reflective attitude, selfmanagement, creativity, innovation, and making decisions on the parts of the students. is proposed and the intervention program of the same nature, as a concretion of the theoretical proposal, show that for the formation of the CSCE in the student of the career under investigation, a close relationship is required between the theoretical component, the practicalexperiential and attitudinal change, based on its contextualized nature and promoting reflection, decision-making, self-management, creativity and innovation of the student.